2018
DOI: 10.1136/bmjopen-2018-021613
|View full text |Cite
|
Sign up to set email alerts
|

An adapted instrument to assess informed consent comprehension among youth and parents in rural western Kenya: a validation study

Abstract: ObjectiveTo adapt and validate a questionnaire originally developed in a research setting for assessment of comprehension of consent information in a different cultural and linguistic research setting.DesignThe adaptation process involved development and customisation of a questionnaire for each of the three study groups, modelled closely on the previously validated questionnaire. The three adapted draft questionnaires were further reviewed by two bioethicists and the developer of the original questionnaire fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 22 publications
(20 reference statements)
0
10
0
Order By: Relevance
“…Thus, in future studies, tools such as the Digitised Informed Consent Comprehension Form should be used to measure patient understanding. 7 Agre and Rapkin investigated the effect of informed consent tools, including written and online materials, videos, and booklets, on patient understanding of informed consent. 2 They found that the provision of different media tools did not result in higher patient information status than that of patients informed using routine written tools.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, in future studies, tools such as the Digitised Informed Consent Comprehension Form should be used to measure patient understanding. 7 Agre and Rapkin investigated the effect of informed consent tools, including written and online materials, videos, and booklets, on patient understanding of informed consent. 2 They found that the provision of different media tools did not result in higher patient information status than that of patients informed using routine written tools.…”
Section: Discussionmentioning
confidence: 99%
“…Reliability means that the measurement tool re ects the consistency and stability of the measurement results, and the Cronbach's alpha coe cient and the split-half reliability (0.7-0.9) re ect the internal consistency of the questionnaire [18] . Test-retest reliability (> 0.8) re ects the stability of the questionnaire [19] . The Cronbach's alpha coe cients of this questionnaire and each dimension were 0.948, 0.976, 0.966, 0.910, and the split-half reliability was 0.951, indicating that the questionnaire had a good degree of consistency.…”
Section: Exploratory Factor Analysismentioning
confidence: 99%
“…Reliability means that the measurement tool re ects the consistency and stability of the measurement results, and the Cronbach's alpha coe cient and the split-half reliability (0.7-0.9) re ect the internal consistency of the scale [18] . retest reliability (> 0.8) re ects the stability of the scale [19] . The Cronbach's alpha coe cients of this scale and each dimension were 0.948, 0.976, 0.966, 0.910, and the split-half reliability was 0.951, indicating that the scale had a good degree of consistency.…”
Section: Reliability Testmentioning
confidence: 99%